Comparison of respiratory toxicity of TiO2 and Fe3O4 nanoparticles after intravenous instillation: an experimental study - Hurbánková, Marta; Romančíková, Dominika; Volkovová, Katarína; Wimmerová, Soňa; Moricová, Štefánia (Central European Journal of Public Health, 2020)
OBJECTIVE: Nanomaterials consist of particles smaller than 100 nm - nanoparticles (NPs). Their nano dimensions allow them to penetrate through various membranes and enter into the bloodstream and disseminate into different body organs. Massive expansion of nanotechnologies together with production of new nanoparticles which have not yet been in contact with living organisms may pose a potential health problem. It is therefore necessary to investigate the health impact of NPs after experimental exposure. Comparison of the effect of TiO2 and NPs Fe3O4 in Wistar rats at time intervals 1, 7, 14 and 28 days was performed by studying the cytotoxic effect in the isolated inflammatory cells from bronchoalveolar lavage (BAL). METHODS: Wistar rats were intravenously (i.v.) given a suspension of NPs TiO2 or Fe3O4 (coated by sodium oleate) via the tail vein. After time intervals of 1, 7, 14 and 28 days, we sacrificed the animals under anaesthesia, performed BAL and isolated the cells. The number of animals in the individual groups was 7-8. We examined the differential count of BAL cells (alveolar macrophages - AM, polymorphonuclear leukocytes - PMN, lymphocytes - Ly); viability and phagocytic activity of AM; the proportion of immature and polynuclear cells and enzymes - cathepsin D - CAT D, lactate dehydrogenase - LDH and acid phosphatase - ACP. RESULTS: We found that TiO2 NPs are relatively inert - without induction of inflammatory and cytotoxic response. Exposure to nanoparticles Fe3O4 induced - under the same experimental conditions - in comparison with the control and TiO2 a more extensive inflammatory and cytotoxic response, albeit only at 1, 7 and 14 days after injection. CONCLUSIONS: The results suggest that TiO2 and Fe3O4 nanoparticles used in our study were transferred from the bloodstream to the respiratory tract, but this effect was not observed at 28 days after i.v. injection, probably due to their removal from the respiratory tract.
Keywords: titan; krysa rodu Rattus; Animals; Ferrosoferric Oxide; kovové nanočástice; Titanium; zvířata; Administration, Intravenous; Rats, Wistar; Metal Nanoparticles; nemoci dýchací soustavy; Rats; Respiratory Tract Diseases; oxid železnato-železitý; potkani Wistar; intravenózní podání